THE DECADE-LONG INSTABILITIES IN EARTH’S ROTATION AS EVIDENCE OF LITHOSPHERIC DRIFT OVER THE ASTENOSPHERE - Sidorenkov, N. S. (Одеські астрономічні публікації, 2016)
The decade instabilities in Earth’s rotation (DIER) are usually explained by the interactions of the Earth’s core and mantle. This hypothesis explains well a close correlation between DIER and the variations in the rate of the westward drift of the geomagnetic eccentric dipole; it corresponds quite reasonably to the possible redistribution of the angular momentum between the fluid core and the mantle of the Earth. however, the hypothesis can not explain the close correlations of DIER with the observable variations in the masses of the Antarctic andGreenlandice sheets, with the decade oscillations of the types of synoptic processes (the epochs of the atmospheric circulation), with the anomalies of the global temperature, regional anomalies of the cloudiness, precipitation, and other climatic characteristics. It is supposed that the DIER are the fluctuations of the velocity of the lithosphere driftage along the asthenosphere. The sliding of the lithosphere over the asthenosphere is possible due to of the vibratory displacement mechanism by tidal forces. The consequences following from this hypothesis are discussed.